2002
DOI: 10.1038/sj.ejcn.1601304
|View full text |Cite
|
Sign up to set email alerts
|

The effect of nutritional intervention in elderly subjects residing in group-living for the demented

Abstract: Objectives: We studied the nutritional status and the effects of nutritional intervention on body weight, cognition and activities of daily life (ADL)-function in demented individuals. Design: Controlled non-randomised study. Setting: Group-living for demented elderly (GLD), ie community assisted housing. Subjects and interventions: Twenty-two residents living in one of two units (GLD-I), received oral liquid supplements (1720 kJ=410 kcal=day) and the personnel of the GLD-I were given nutritional education. Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
99
1
4

Year Published

2003
2003
2012
2012

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(110 citation statements)
references
References 38 publications
(44 reference statements)
2
99
1
4
Order By: Relevance
“…Beck, Ovesen & Schroll (32), after 6 months' prospective follow-up of patients aged 65 years and older from general practice, concluded that a high percentage of the old, especially those initially malnourished, will not benefit from nutritional support if the basic causes of their malnutrition are not identified. Faxen-Irving et al (25) carried out a study in a group home for demented elderly, in community-assisted housing. The nutritional treatment did not affect the rate of decline in cognitive function or Katz' ADL index.…”
Section: Identifying Signs Of An Early Stage Of Undernutrition In a Hmentioning
confidence: 99%
“…Beck, Ovesen & Schroll (32), after 6 months' prospective follow-up of patients aged 65 years and older from general practice, concluded that a high percentage of the old, especially those initially malnourished, will not benefit from nutritional support if the basic causes of their malnutrition are not identified. Faxen-Irving et al (25) carried out a study in a group home for demented elderly, in community-assisted housing. The nutritional treatment did not affect the rate of decline in cognitive function or Katz' ADL index.…”
Section: Identifying Signs Of An Early Stage Of Undernutrition In a Hmentioning
confidence: 99%
“…Dietary intake was, however, not assessed (Faxén-Irving et al, 2002;Bonnefoy et al, 2003), or was assessed only at baseline (van-der-Wielen et al, 1995;Wouters-Wesseling et al, 2002). Other studies were mostly conducted in freeliving individuals and were of short duration (McKay et al, 2000) or were without a placebo treatment (Gray Donald et al, 1995;Krondl et al, 1999;Payette et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, a combination of nutritional supplements and an education programme may have been more effective in this population group. For example, in another study, 5 months after such combined intervention in residents of group living for the demented, a weight gain of 3.5 kg was observed (Faxén-Irving et al, 2002).…”
Section: Discussionmentioning
confidence: 95%